Hospitalist workload influences faculty evaluations by internal medicine clerkship students - Robinson RL (Advances in Medical Education and Practice, 2015)
Robert L Robinson Department of Internal Medicine, Southern Illinois University School of Medicine, Springfield, Illinois, USA Background: The last decade has brought significant changes to internal medicine clerkships through resident work-hour restrictions and the widespread adoption of hospitalists as medical educators. These key medical educators face competing demands for quality teaching and clinical service intensity. Objective: The study reported here was conducted to explore the relationship between clinical service intensity and teaching evaluations of hospitalists by internal medicine clerkship students. Design: A retrospective correlation analysis of clinical service intensity and teaching evaluations of hospitalists by internal medicine clerkship students during the 2009 to 2013 academic years at Southern Illinois University School of Medicine was conducted. Participants: Internal medicine hospitalists who supervise the third-year inpatient experience for medical students during the 2009 to 2013 academic years participated in the study. Measures: Clinical service intensity data in terms of work relative value units (RVUs), patient encounters, and days of inpatient duty were collected for all members of the hospitalist service. Medical students rated hospitalists in the areas of patient rapport, enthusiasm about the profession, clinical skills, sharing knowledge and skills, encouraging the students, probing student knowledge, stimulating independent learning, providing timely feedback, providing constructive criticism, and observing patient encounters with students. Results: Significant negative correlations between higher work RVU production, total patient encounters, duty days, and learner evaluation scores for enthusiasm about the profession, clinical skills, probing the student for knowledge and judgment, and observing a patient encounter with the student were identified. Higher duty days had a significant negative correlation with sharing knowledge/skills and encouraging student initiative. Higher work RVUs and total patient encounters were negatively correlated with timely feedback and constructive criticism. Conclusion: The results suggest that internal medicine clerkship student evaluations of hospitalist faculty are negatively influenced by high clinical service intensity measured in terms of annual work RVUs, patient encounters, and duty days. Keywords: work relative value units, patient encounters, duty days, clinical service intensity, medical students